Factors Influencing Mathematics Learning: Path Analysis - Anggun Badu Kusuma; Heri Retnawati (EduMa: Mathematics education learning and teaching, 2022)
The factors that influence the learning of mathematics are very diverse. On this occasion, the focus is on gender, learning styles, learning independence, and motivation. These factors are fascinating because they always appear in learning and research themes. This study aimed to examine how the influence of these factors on learning achievement. This research is associational research which is a descriptive research methodology. The research subjects are 5th-semester students who take calculus courses, mathematics education study program, Universitas Muhammadiyah Purwokerto. The instruments used in this study were questionnaires and learning outcomes tests. To analyze the data used, LISREL (Linear Structural Relationship) software. The results showed that not all variables affect each other directly. Gender influences learning motivation. Learning style has an impact on learning motivation. Learning motivation affects learning independence. Learning independence influences learning achievement. Learning motivation influences learning achievement. If it is seen how they influence learning achievement, then learning motivation has the most significant impact compared to gender, learning style, and learning independence.